Examining the role of English language proficiency, language learning anxiety, and self-regulation skills in EMI students’ academic success - Yuksel, Dogan; Soruç , Adem; Horzum, Barıs; McKinley, Jim (Studies in Second Language Learning and Teaching, 2023)
This study focuses on the predictive power of linguistic (i.e., general English proficiency; identified simply as “proficiency” in this paper) and non-linguistic (i.e., language learning anxiety and self-regulation) factors on the academic success of English medium instruction (EMI) students studying in engineering and social sciences programs in a Turkish university setting. Data were collected from 705 conveniently sampled EMI students of four academic subjects (international relations; N = 158; business administration; N = 184; mechatronics engineering; N = 181; mechanical engineering: N = 182) representing two disciplines (i.e., social sciences and engineering) from a public university. Pearson correlation and SEM analyses were run to determine the relationships among language learning anxiety, self-regulation, proficiency and EMI success. Findings revealed that anxiety and self-regulation skills do affect EMI students’ proficiency irrespective of academic disciplines. Both self-regulation and proficiency impacted EMI students’ academic success in engineering, while only proficiency predicted academic success in the social sciences. These results are discussed and pedagogical implications are given related to the impact of linguistic and non-linguistic factors in EMI contexts.